THE MATURE STUDENTS’ GUIDE TO READING AND COMPOSITION (Authors: Delores H. Lipscomb, Judith I. Martin, Allee J. Robinson); COMMUNICATION: A GUIDE TO COMPOSITION AND READING (Authors: Delores H. Lipscomb, Judith I. Martin, Allee J. Robinson, and Charles Franklin) - Cook, Donna Logsdon (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1980)
Delores H. Lipscomb, Judith I. Martin, Allee J. Robinson. THE MATURE STUDENTS’ GUIDE TO READING AND COMPOSITION. Willowdale, Ontario: Science Research Associates (Canada) Limited, 1975. 280 pp. 6.85. Delores H. Lipscomb, Judith I. Martin, Allee J. Robinson, and Charles Franklin. COMMUNICATION: A GUIDE TO COMPOSITION AND READING. Willowdale, Ontario: Science Research Associates (Canada) Limited, 1975. 196 pp. 6.85.